Future considerations for contextualising force plate test results in professional football - McMahon, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Commercial force plate (FP) systems are now common in professional football codes and are often used daily to assess athletes. Practitioners, such as sport scientists and physiotherapists, are responsible for administering FP tests, but there are few quality resources and published studies available to guide their interpretation of the results. As professional football clubs are private companies, they are solely responsible for tests conducted with their athletes, without industry-wide performance standards or regulations to abide by. Various FP tests (mainly vertical jump and multi-joint isometric tests) are broadly applied in football for benchmarking athletes` performance, informing and evaluating exercise interventions, monitoring neuromuscular (NM) fatigue, and guiding injured athletes` return to play. Jump height is mostly reported as the primary outcome measure for vertical jump tests, but it may mask subtle acute and chronic alterations in NM strategies which variables derived from FP measurements can illuminate. Also, jump height is biased towards lighter athletes and may not be a fair metric for comparing athletes` performances when there are large variations in body mass, such as is in rugby. Jump height alone will also not reflect any changes in body mass that occur between testing occasions, which is especially relevant for maturing youth athletes or adult athletes who complete a hypertrophy-focussed training programme. Additionally, youth athletes who grow in height between testing occasions will be afforded with a greater distance over which to apply force to their mass, which may alter their NM strategy and/or their jump height score. In multi-joint isometric tests, the peak forces attained may require scaling to body mass depending on the football code, position and intended application. Thus, there is a requirement to better contextualise popular FP test results in football to inform practitioner decision making. The presentation will include key results from several ongoing FP studies that have been funded either by a leading commercial FP company or the English Football Association. A comprehensive FP testing battery has been completed for 200 professional football athletes across the domestic season and international tournaments. The data is contextualised to facilitate quick and accurate decision making via a variety of statistical approaches (e.g., standardised scores) and data visualisation tools (e.g., traffic light systems). The results highlight future considerations using FPs in football for benchmarking athletes` performances, seasonal monitoring to inform supercompensation and/or chronic fatigue, and acute fatigue monitoring both pre- and post-match and when fixture congestion is high. The target audience is sport science and medicine practitioners and researchers who routinely assess athletes with FPs, particularly footballers, and any delegate who is interested in conducting physical performance tests in sport.